A randomized phase II trial of doxorubicin plus pemetrexed followed by docetaxel versus doxorubicin plus cyclophosphamide followed by docetaxel as neoadjuvant treatment of early breast cancer - Schneeweiss, Andreas; Marmé, Frederik; Ruiz, A.; Manikhas, A. G.; Bottini, A.; Wolf, M.; Sinn, Peter; Mansouri, K.; Kennedy, L.; Bauknecht, T. (Annals of oncology, 2011)
Background - Neoadjuvant systemic therapy (NST) before surgery is a standard option for patients with early breast cancer (EBC) that allows in vivo chemosensitivity testing. Given the promising activity of pemetrexed plus doxorubicin in metastatic breast cancer, it was reasonable to evaluate the utility of this combination as part of an NST regimen in EBC. - Patients and methods - Patients with untreated operable T2-T4a-c N0-2 M0 breast cancer were randomly assigned to receive either four cycles of pemetrexed 500 mg/m2 plus doxorubicin 60 mg/m2 every 3 weeks (q3w) followed by four cycles of docetaxel 100 mg/m2 q3w (AP-D) or four cycles of doxorubicin 60 mg/m2 plus cyclophosphamide 600 mg/m2 q3w followed by four cycles of docetaxel 100 mg/m2 q3w (AC-D). Surgery was carried out within 2 months after last chemotherapy. Primary end point was pathological complete response (pCR) rate in the breast. Secondary end points included clinical response rate, rate of histologically negative axillary lymph nodes, toxicity, and disease-free survival. - Results - From September 2005 to August 2007, 257 patients were randomly allocated to 17 sites. Median age was 48 and 49 years for AP-D and AC-D, respectively. Overall pCR rates were 16.5% for AP-D and 20.2% for AC-D. With AP-D, pCR rate was 17.8% for hormone receptor (HR)-negative patients and 15.9% for HR-positive patients. With AC-D, pCR rates were 42.9% and 7.8% for HR-negative and HR-positive patients, respectively. Clinical response rates were 59.5% in the AP-D group and 68.1% in the AC-D group. The rate of histologically negative axillary lymph nodes was 53% in both groups. Both treatments were well tolerated. Median disease-free survival is currently not mature. - Conclusions - AP-D and AC-D are well tolerated and active as NST in EBC. Of note, AC-D had a higher pCR rate in HR-negative tumors, whereas AP-D had more activity if HRs were expressed.